Energy conservation and sustainability at Adobe Systems Incorporated. Issue 3 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to analyze a successful sustainability program run by an owner that has invested $23 million, received rebates of $10 million, accrued over $9 million of savings and has won top scores in LEED and Energy Star. Other owners planning to invest in energy conservation and sustainability can apply the lessons learnt to overcome common barriers.Design/methodology/approach – This case study is based on project information supplied by the owner and structured interviews with the operational team. The projects are analyzed based on drivers and payback characteristics. Finally, the case study puts Adobe Systems' results within the context of the industry by matching it to the challenges identified in other reports.Findings – The results show that 40 percent of projects are initiated by operation management personnel. The projects with the biggest savings are supported by third‐party incentives. Only 10 percent of projects are evaluated by simulation and account for 12 percent of annual savings. Energy Star plays a crucial role for benchmarking performance and should be run annually. LEED EB is valuable when expending conservation efforts beyond energy aspects to sustainability. Performance benchmarking is a crucial step to determine the potential and priority of energy improvements.Research limitations/implications – The findings are based on the three towers in San Jose, California.Practical implications – Building owners can incorporate the methodologies applied to evaluate these successful projects into their buildings. Facility managers can leverage the findings to present the advantages of recertification and commissioning.Originality/value – A detailed project analysis, from a leader in practice, shows the importance of the local building operations team in sustainability and energy conservation. Acknowledgements : The authors thank Randall Knox, III at Adobe for setting up the case study and granting access to data required for the report. They also thank George Denise, Karl Okulove and Lakshmi Meera Ramanathan at Cushman & Wakefield for their time, insights, and validation of the findings.